2007
DOI: 10.11646/zootaxa.1565.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Ostracoda (Myodocopa) from Anchialine Caves and Ocean Blue Holes

Abstract: Eleven stygobitic myodocopid ostracodes (two new–Danielopolina palmeri and Spelaeoecia hox) in the Order Halocyprida are reported from anchialine waters in 11 inland blue holes in Bahamas. One stygobitic halocyprid ostracode is reported from two localities in Bermuda, and one from a cave in Mexico. A new subfamily, Spelaeoeciinae, is proposed to contain the genus Spelaeoecia, and the subfamily Deeveyinae is elevated to family status. Two new species of cladocopid ostracode (Pseudopolycope helix and Pontopolyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…varies between species when taxonomic drawings are compared, but Kornicker et al (2007) concluded that when the antennule is extended horizontally outside the carapace, the first and second segments form a linear arrangement, but when partly withdrawn these two segments sit at a right angle to one another. The majority of characters relate to the presence or absence of specific setation elements (Fig.…”
Section: Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…varies between species when taxonomic drawings are compared, but Kornicker et al (2007) concluded that when the antennule is extended horizontally outside the carapace, the first and second segments form a linear arrangement, but when partly withdrawn these two segments sit at a right angle to one another. The majority of characters relate to the presence or absence of specific setation elements (Fig.…”
Section: Speciesmentioning
confidence: 99%
“…Together with a diverse array of other crustacean taxa including thermosbaenaceans, remipedes, and epacteriscid and speleophriid copepods (Wagner, 1994;Boxshall and Jaume, 2000;Fosshagen et al, 2001;Kornicker et al, 2007), Danielopolina is treated as a member of this core anchialine faunal suite (referred to as the Remipede Type by Humphreys and Danielopol (2006). The discovery of one representative of this core fauna in an anchialine habitat has been used as an indication that others will be present: for example, after the discovery of a species of the thermosbaenacean genus Halosbaena Stock, 1976 in northwestern Australia, Wagner (1994) predicted that Danielopolina would also be found there -a prediction confirmed six years later by Danielopol et al (2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the remipede genus Speleonectes currently includes 12 described species, 2 of which are from Lanzarote in addition to 7 species in the Bahamas and 1 each from Yucatan, Cuba and the Dominican Republic (Koenemann et al this issue). Similarly, the halocyprid ostracode genus Danielopolina consists of 12 species, with 2 from Lanzarote, D. wilkensi and D. phalanx, 4 from the Bahamas, and 1 each from Yucatan, Cuba, Jamaica, Galapagos, Western Australia, Christmas Island, and the deep sea of the South Atlantic (Kornicker et al 2007). Congeners of the thermosbaenacean Halosbaena fortunata from Lanzarote are known from Venezuela, Curaçao, and Western Australia (Poore and Humphreys 1992) and, most recently, Okinawa, Japan (Shimomura and Fujita 2009).…”
Section: Origin Of the Lava Tube Faunamentioning
confidence: 99%
“…However, several studies have addressed the diversity of Crustacea in anchialine caves of the Caribbean (Jaume et al 1998;Iliffe 2003, 2007;Koenemann et al 2003;Iliffe and Botosaneanu 2006;Kornicker et al 2007), which is higher than the diversity of Crustacea in the Corona lava tube ( Table 3).…”
Section: Fauna Compositionmentioning
confidence: 99%